Main-d’œuvre dans le secteur de la santé au Canada : Pistes d’action futures - Académie canadienne des sciences de la santé (2023)
L’Académie canadienne des sciences de la santé (ACSS) fournit en temps utile des évaluations indépendantes qui éclairent l’élaboration des politiques et des pratiques visant à répondre aux préoccupations pressantes qui touchent la santé des Canadiennes et des Canadiens. L’ACSS contribue à concrétiser un changement en faveur d’un Canada en meilleure santé. Santé Canada a financé l’Académie canadienne des sciences de la santé pour évaluer, en se fondant sur des données probantes, des pistes d’action futures qui permettront de résoudre la crise liée à la main-d’œuvre dans le secteur de la santé. Au cours de cette évaluation indépendante d’une année, les auteurs ont examiné plus de 5 000 articles scientifiques et 250 rapports de politique, et consulté quelque 800 personnes représentant plus de 245 organisations à travers le Canada. Le travail, également guidé par un groupe pluridisciplinaire diversifié comptant plus de 30 spécialistes cliniques et universitaires sur la main-d’œuvre dans le secteur de la santé, a abouti à la rédaction du présent rapport revu par des pairs. Le rapport se penche sur les thèmes suivants : soutien et maintien des effectifs, déploiement et prestation des services, et planification et développement, tout en étudiant les questions propres aux peuples autochtones, aux collectivités rurales et éloignées, et aux populations systématiquement défavorisées, et propose cinq pistes d’action prioritaires pour une mise en œuvre anticipée, établies à partir des 26 politiques et pratiques stratégiques principales cernées. C'est sous le thème des populations systématiquement défavorisées que le rapport, au point 4.1.4.2, souligne l'importance d’« assurer un accès équitable aux soins adaptés aux spécificités linguistiques », ce qui souligne l’importance d’une concordance linguistique dans les soins de santé. Il recommande de permettre aux professionnels de la santé d’assurer la prestation de soins adaptés aux spécificités culturelles et linguistiques grâce à des programmes d’études et de formation, ainsi qu’à des outils et ressources spécifiques, étayés par des changements de politiques et de procédures.
pages: 281

Faits saillants sur la langue française au Manitoba en 2021 - Auclair, Nicolas; Frigon, Catherine; St-Amand (Statistique Canada, 2023)
Ce document présente des données sur la répartition de la population francophone au Manitoba d'après le recensement de 2021, fournissant ainsi des informations utiles pour évaluer les besoins en matière de santé de cette population.
pages: 14

Faits saillants sur la langue française en Alberta en 2021 - Auclair, Nicolas; Frigon, Catherine; St-Amand, Gabriel (Statistique Canada, 2023)
Ce document présente des données sur la répartition de la population francophone en Alberta d'après le recensement de 2021, fournissant ainsi des informations utiles pour évaluer les besoins en matière de santé de cette population.
pages: 14

Faits saillants sur la langue française en Colombie-Britannique en 2021 - Auclair, Nicolas; Frigon, Catherine; St-Amand, Gabriel (Statistique Canada, 2023)
Ce document présente des données sur la répartition de la population francophone en Colombie-Britannique d'après le recensement de 2021, fournissant ainsi des informations utiles pour évaluer les besoins en matière de santé de cette population.
pages: 14

Faits saillants sur la langue française en Saskatchewan en 2021 - Auclair, Nicolas; Frigon, Catherine; St-Amand, Gabriel (Statistique Canada, 2023)
Ce document présente des données sur la répartition de la population francophone en Saskatchewan d'après le recensement de 2021, fournissant ainsi des informations utiles pour évaluer les besoins en matière de santé de cette population.
pages: 14

Key facts on the French language in Alberta in 2021 - Auclair, Nicolas; Frigon, Catherine; St‑Amant, Gabriel (Statistics Canada, 2023)
This document presents information on the distribution of the French Speaking population in Alberta according to the 2021 census, providing useful information to estimate health needs for this population.
pages: 14

Key facts on the French language in British Columbia in 2021 - Auclair, Nicolas; Frigon, Catherine; St‑Amant, Gabriel (Statistics Canada, 2023)
This document presents information on the distribution of the French Speaking population in British Columbia according to the 2021 census, providing useful information to estimate health needs for this population.
pages: 14

Key facts on the French language in Manitoba in 2021 - Auclair, Nicolas; Frigon, Catherine; St‑Amant, Gabriel (Statistics Canada, 2023)
This document presents information on the distribution of the French Speaking population in Manitoba according to the 2021 census, providing useful information to estimate health needs for this population.
pages: 14

Key facts on the French language in Saskatchewan in 2021 - Auclair, Nicolas; Frigon, Catherine; St‑Amant, Gabriel (Statistics Canada, 2023)
This document presents information on the distribution of the French Speaking population in Saskatchewan according to the 2021 census, providing useful information to estimate health needs for this population.
pages: 14

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods. Interpretation: French-only speakers in Ottawa face modest — but statistically significant — overall inequities in travel burden when accessing primary care, compared with the general population, and higher inequities in specific neighbourhoods. Our results are of interest to policy-makers and health system planners, and our methods can be replicated and used as comparative benchmarks to quantify access disparities for other services and regions across Canada.

Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario) - Benoît, Josée; Dagnogo, Djenaba Sarah; Renaud, Alexandre (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2023)
Le recrutement, l’intégration et la rétention de la main-d’œuvre en santé ayant les compétences linguistiques vices en français constituent des défis importants auxquels font face un grand nombre d’organismes de santé. En 2014-2018, Communauté accueillante faisait partie d’un projet pilote pour favoriser le recrutement et la rétention de ressources humaines bilingues dans le domaine de la santé et des services sociaux dans le sud de l’Ontario. Ce projet a permis la création de cinq communautés de pratique qui pouvaient regrouper les professionnel·les bilingues d’agences de santé et services sociaux, des étudiant·es bilingues provenant des programmes de soins infirmiers, travail social, médecine, psychologie, orthophonie et autres programmes identifiés dans les régions, les collèges et universités francophones et anglophones qui offrent ces programmes partout en Ontario, ainsi que les professionnel·les bilingues de la santé et des services sociaux qui désirent être informé·es des ressources communautaires et opportunités de carrières dans ces régions. Les cinq communautés de pratique faisant partie du projet pilote Communauté accueillante 2.0 ont mis en place des stratégies et des activités qui leur sont propres, selon les besoins de leur région, permettant le partage de ressources, d’expertises, de connaissances et de pratiques innovantes inter-régions, mais également un partage de ressources entre paliers. Par exemple, des informations venant de la Société Santé en français ou de Santé Canada pouvaient facilement être distribuées entre les régions. En 2023, afin de diffuser les leçons tirées de ce projet, le Réseau franco-santé du Sud de l’Ontario a produit une ressource d’apprentissage intégrée à la Plateforme accès éQUITÉ dans le but d’appuyer le travail collaboratif mené en communautés de pratique pour concevoir des stratégies permettant d’accroître l’offre des services de santé en français dans les communautés francophones en situation minoritaire.
fs-ref-orig: Benoît, J., Dagnogo, D.S. & Renaud, A. (2023, mise à jour 2025). Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Benoit-2025f

La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances - CAMH-Evidence Exchange Network (2023)
fs-ref-orig: CAMH-Evidence Exchange Network. (2023). La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances. https://kmb.camh.ca/fr/eenet/documentation/la-recherche-en-temps-reel-projet-echo-pour-francophones fs-code-orig: CAMH-Evidence Exchange Network-2023a

Research as it Happens : ECHO project for Francophones - Assessing the needs of service providers working with Franco-Ontarian communities to create a French-language, substance use management training program - CAMH-Evidence Exchange Network (2023)

Canada’s Health Workforce: Pathways Forward - Canadian Academy of Health Sciences (2023)
The Canadian Academy of Health Sciences (CAHS) provides independent and timely assessments that inform policy and practice to address critical health challenges affecting Canadians. The CAHS helps put change into action for a healthier Canada. Health Canada funded the Canadian Academy of Health Sciences to undertake an evidence-based assessment of possible pathways forward to ease the health workforce crisis. This arms-length assessment involved reviewing more than 5,000 academic articles and 250 policy reports, and consulting more than 800 individuals from 245 organizations across Canada within a year. The assessment was guided by a diverse group of more than 30 interdisciplinary clinical and academic health workforce experts and culminated in this peer-reviewed report. This report covers support and retention, deployment and service delivery, and planning and development with particular consideration of Indigenous Peoples, rural and remote communities, and systemically disadvantaged populations. Five priority pathways for early implementation are suggested, which emerged from the 26 evidence-based leading policies and practices that were identified. Under the theme of systematically disadvantaged populations, the report, in section 4.1.4.2, emphasises the importance of ‘ensuring equitable access to care tailored to linguistic specificities’, which highlights the importance of linguistic appropriateness in healthcare. It recommends enabling healthcare practitioners to provide culturally and linguistically safe care through curricula, training programs, tools, and resources that are reinforced by policy and procedure changes.
pages: 263

L'offre active de services de santé mentale en français en Ontario et au Manitoba : les rôles clés des instruments et des outils - Cardinal, Linda; de Moissac, Danielle; Deschênes-Thériault, Guillaume (Administration publique du Canada / Canadian Public Administration, 2023)
Cet article présente les données d'un sondage réalisé en 2019 sur la connaissance des gestionnaires et des professionnels œuvrant dans le domaine de la santé mentale en Ontario et au Manitoba de leurs obligations linguistiques et des outils qui favorisent la pratique de l'offre active de services français. L'étude permet de souligner que plus les professionnels et les gestionnaires comprennent leurs obligations, tant en Ontario qu'au Manitoba, plus ils peuvent profiter des outils existants pour s'en acquitter. L'étude montre qu'il existe en effet un lien entre la connaissance des obligations et l'utilisation des outils pour faire de l'offre active de services de santé mentale en français. Elle permet aussi d'insister sur le rôle clé des outils pour faire de l'offre active de services en français.

Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

L'immigration francophone en milieu minoritaire : pour une démarche audacieuse, coordonnée et renforcée - Comité sénatorial permanent des langues officielles, Sénat du Canada (Comité sénatorial permanent des langues officielles, 2023)
Le poids démographique de la francophonie canadienne décline. La solution pour la survie et l’épanouissement des communautés francophones en situation minoritaire passe en grande partie par l’immigration. Le Comité sénatorial permanent des langues officielles présente dans ce rapport le portrait de la situation et les préoccupations des intervenants concernant l’immigration francophone en milieu minoritaire, qui a fait l’objet de plusieurs engagements du gouvernement fédéral ces dernières années. Il présente également 12 recommandations élaborées sur la base des mémoires et des témoignages de plus d’une cinquantaine d’intervenants de divers milieux. Bien que le rapport ne soit pas spécifique au domaine de la santé, plusieurs des points soulevés dans le rapport portent sur la nécessité de porter une attention particulière aux besoins en matière de main d’œuvre francophone dans les secteurs de l’éducation, de la petite enfance et de la santé.
Nombre de pages: 87

Bien dans notre peau: Élaboration d’un outil de diagnostic pour informer la conception et l’évaluation de services et partenariats sécuritaires, inclusifs et équitables pour toute personne 2ELGBTQ+ d’expression française au Manitoba - Courcelles, Rémi; Hardy, Stephan; Prada, Kevin (Collectif LGBTQ* du Manitoba, 2023)
Comment pallier le risque accru de discrimination ou de stigmatisation auquel font face les membres de la Communauté dans leurs recours aux services ou dans leur participation aux événements, surtout en collaboration avec des organismes non francophones ou non 2ELGBTQ+ ? En quoi consistent concrètement l’accessibilité, l’inclusion et les pratiques prometteuses concernant l’offre de services sociaux et de santé destinés aux membres de la Communauté? Et selon quels critères objectifs établir des partenariats, concevoir des services ou encore évaluer et améliorer des services existants? Le présent projet a visé à répondre à ces questions, par le biais d’un nouvel outil de diagnostic. Le présent rapport présente premièrement la démarche qui a été entreprise pour développer cet outil de diagnostic. Il présente ensuite l’outil tel qu’il s’applique aux trois volets (santé, épanouissement social et culturel, éducation). Nous passons ensuite en revue les limites du projet actuel et proposons des recommandations pour les suivis à entreprendre. Ce rapport sert donc à la fois d’outil analytique à l’état d’essai et de plan d’action pour le Collectif afin de poursuivre la mise en œuvre des recommandations du rapport « Des nôtres »
Nombre de pages: 40

English-language Health and Social Services Access in Québec. Comparison 2019-2023 - CROP (Community Health & Social Services Network, 2023)

Qui sont nos tout-petits? Portrait des enfants de langue française âgés entre 0 et 6 ans et leur famille habitant dans le territoire du Yukon - 2e édition - Dault, Mylène (Partenariat communauté en santé, 2023)
Ce rapport dresse un portrait des enfants de langue française du Yukon âgées de 0 à 6 ans. Les données présentées proviennent du recensement de 2021,
Nombre de pages: 22

Care Trajectories for Yukon Francophone Seniors - De Moissac, Danielle (Parteneriat communauté en santé, 2023)
Over the past several years, the Yukon Government has been exploring the matter of aging in place for its senior citizens (Government of Yukon, 2019). In the 2018 report entitled Yukon Health Status Report – Focus on Seniors, the Government of Yukon (2018) presented a profile of the health and well-being of Yukon seniors. t is important to note, however, that the voice of Francophone seniors is neither represented in the Focus on Seniors report (Government of Yukon, 2018) nor in the public engagement documentation, except for the mention of a liaison service for Francophones when discharged from the hospital (Government of Yukon, 2018 What we Heard About Aging in Place., p. 26). Although Francophones were able to participate in the engagement process, no mention was made about any specific needs of Francophone seniors. In light of the fact that Francophone seniors living in a minority language situation are aging at a proportionally faster rate than the overall Canadian population (Bouchard et al., 2015) and that this results in increased use of home care and other services (Van Kemenade, Bouchard & Bergeron, 2015), the needs of seniors from both of Yukon’s official language groups must be considered. This report provides information to further our understanding of this matter. Report Objectives: 1) To present findings related to Yukon Francophone senior care trajectories, from the moment when they first perceive the need for support with their overall health, on the physical as well as the mental and social levels. 2) To identify the care, health, and social service needs of these seniors, according to the services available, such that the active offer of French language services meets their needs.
Nombre de pages: 22

Trajectoires de soins pour les aîné(e)es francophones du Yukon - de Moissac, Danielle (Partenariat communauté en santé, 2023)
Le gouvernement du Yukon s’intéresse depuis quelques années à la question du vieillissement chez soi pour sa population aînée (gouvernement du Yukon, 2019). Un rapport publié en 2018 intitulé Yukon Health Status Report: Focus on Seniors (Gouvernement du Yukon, 2018) présente le profil de santé et de mieux-être des aîné·e·s du territoire. Force est de constater, toutefois, que la voix des francophones n’est représentée ni dans le rapport sur la santé des aîné·e·s (Gouvernement du Yukon, 2018) ni dans les écrits émanant des consultations, autrement que par la mention d’un service de liaison pour les francophones à leur congé de l’hôpital (p. 26, Gouvernement du Yukon, 2018 What we Heard About Aging in Place.). Bien que des francophones aient pu participer aux consultations, aucune trace des besoins spécifiques des aîné·e·s de la francophonie n’est rapportée. Sachant que la population aînée francophone vivant en situation linguistique minoritaire vieillit proportionnellement plus rapidement que l’ensemble de la population canadienne (Bouchard et coll., 2015) et que cela engendre une utilisation accrue de soins à domicile et d’autres services (van Kemenade, Bouchard et Bergeron, 2015), il est important de saisir les besoins des personnes âgées issues des deux groupes de langues officielles du Yukon. Ce présent rapport pourra mieux nous informer à cet égard. Objectifs du rapport: 1) Exposer les constats relatifs aux trajectoires de soins pour les aîné·e·s francophones du Yukon, à partir du moment où ils ressentent le besoin de soutien en lien avec leur santé globale, tant physique que mentale et sociale; 2) Prendre connaissance des besoins de ces aîné·e·s quant aux soins et services sociaux et de santé, en relation avec les services disponibles dans une optique d’offre active de services en français qui répondent à leurs besoins.
Nombre de pages: 22

L'obligation de communiquer en anglais dans les communautés francophones en contexte minoritaire: des futures infirmières issues de l'immigration témoignent de leur expérience en stage. - Duchesne, Claire; Déri, Catherine E.; Benoît, Josée (Minorités linguistiques et sociétés/Linguistic Minorities and Society, 2023)
L’intégration socioprofessionnelle des infirmières de langue française issues de l’immigration est particulièrement souhaitée par les membres des communautés francophones situées dans les provinces et territoires où la langue de la majorité est l’anglais et où les francophones éprouvent de la difficulté à se faire soigner dans leur langue de préférence. Cet article propose une contextualisation des enjeux de l’immigration dans les communautés francophones en contexte minoritaire et, notamment, du besoin d’accueillir des professionnels de langue française dans ces communautés. Des entretiens de recherche réalisés auprès de quatre stagiaires infirmières francophones issues de l’immigration feront état des défis linguistiques qu’elles ont rencontrés dans leurs milieux de stage, particulièrement au regard de la langue anglaise. Enfin, des pistes de solution pour soutenir l’intégration socioprofessionnelle de ces futures infirmières seront également proposées. Mots-clés : infirmières issues de l’immigration, intégration socioprofessionnelle, communautés francophones en contexte minoritaire, formation et stages

Intégration professionnelle des infirmières formées à l’étranger dans les milieux de santé canadiens : une recension défis rencontrés et des pratiques efficaces. - Duchesne, Claire; Le Callonnec, Lucie; Fournier, Janelle; Benoît, Josée; Ben Soltane, Sonia (Revue francophone internationale de recherche infirmière, 2023)
Bien que le besoin de recruter plus de personnel infirmier soit manifeste dans l’ensemble du Canada, les infirmières formées à l’étranger continuent de rencontrer des obstacles à leur intégration dans les milieux des soins de santé. À partir d’une recension des écrits, cet article dresse un portrait des difficultés rencontrées par celles-ci, notamment en ce qui concerne les phénomènes d’acculturation et de racialisation. Il fera par la suite état des pratiques les plus pertinentes afin d’assurer la réussite de leur intégration professionnelle.

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Understanding acceptability of digital health technologies among francophone-speaking communities across the world: a meta-ethnographic study - Gauthier-Beaupré, Amelie; Grosjean, Sylvie (Frontiers in Communication, 2023)
Introduction: Increasingly, people are turning toward digital health technologies to support their care management, communication with health professionals, and performing activities of daily living. Digital health technologies may be well implemented in clinical practices in several jurisdictions, but the influence of sociocultural factors may sometimes be neglected. To increase use and sustainability of these innovative solutions in health care, we need to understand acceptability among diverse groups of the population such as linguistically diverse populations. Francophone-speaking populations in Canada, for example, are known to endure challenges with income, health and difficulties associated with living in rural areas which impede on their likelihood to use digital health technologies. As part of the University of Ottawa International Francophonie Research Chair on Digital Health Technologies, this study aimed to understand the conditions that make digital health technologies acceptable among francophone-speaking communities. Methods: Using a meta-ethnography methodology, this study synthesizes international qualitative research on social acceptability of digital health technology among francophone-speaking communities. We focused on four types of digital health technologies: telemedicine, mobile technologies, wearable technologies, and robotic technologies. Using Noblit and Hare's 7 phase approach to conducting a meta-ethnography, we were able to get a comprehensive synthesis and understanding of the research landscape on the issue. Studies published between 2010 and 2020 were included and synthesized using NVivo, excel and a mind mapping technique. Results: Our coding revealed that factors of social acceptability for digital health technologies could be grouped into the following categories: care organization, self-care support, communication with care team, relational and technical risks, organizational factors, social and ethical values. Our paper discusses the themes evoked in each category and their relevance for the included digital health technologies. Discussion: In discussing the results, we present commonalities and differences in the social acceptability factors of the different digital health technologies. In addition, we demonstrate the importance of considering sociocultural diversity in the study of social acceptability for digital health technologies. Implications: The results of this study have implications for practitioners who are the instigators of digital health technology implementation with healthcare service users. By understanding factors of social acceptability among francophone-speaking communities, practitioners will be better suited to propose and support the implementation of technologies in ways that are suitable for these individuals. For policymakers, this knowledge could be used for developing policy actions based on consideration for diversity.

Les services en français en Ontario en mal de géographie - Gilbert, Anne (Droits, langues et communautés, 2023)

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)
Le présent rapport a été conçu en tant que ressource pour aider l’"Équipe santé Enfants avant tout" à élaborer une stratégie de recrutement, de maintien en poste et de formation des ressources humaines dans la région sanitaire de Champlain, en Ontario. Le rapport a été préparé par l’Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (« l’Institut du savoir »). L’Institut du savoir crée des liens, transmet des connaissances et tire parti de son expertise pour améliorer les compétences des prestataires de services directs et des organismes de l’Ontario afin de renforcer les programmes et les services de santé mentale de l’Ontario pour tous les enfants, les jeunes, les familles et les prestataires de soins. Nous voulions savoir ce que font les organismes — particulièrement ceux du secteur de la santé — pour recruter des prestataires de services qui maîtrisent le français. Nous voulions aussi nous renseigner sur les pratiques de recrutement fondées sur des données probantes décrites dans la littérature. Les stratégies et les principes directeurs présentés dans cette ressource sont tirés d’une analyse contextuelle qui comprenait un examen rapide et non systématique de la littérature. De plus, nous avons consulté des intervenant.e.s clés et des leaders dans le domaine qui ont une expérience directe de recrutement de prestataires de services qui maîtrisent le français.
Nombre de pages: 23

Exploring Primary Care Physicians’ Experiences of Language and Cultural Discordant Care for Linguistic Minority Patients at the End-of-Life: A Study Protocol - Lee, Seung Heyck; Gibb, Maya; Karunananthan, Sathya; Cody, Margaret; Tanuseputro, Peter; Johnston, Sharon; Kendall, Claire; Bedard, Daniel; Collin, Stéphanie; Kehoe MacLeod, Krystal (International Journal of Qualitative Methods, 2023)
Health disparities exist across different linguistic groups. Language barriers in primary care can negatively affect access to healthcare services and the quality and safety of care at the end-of-life. This study will take a novel, in-depth look at the experience of language- and/or cultural-discordant care for adults from linguistic minority groups through the eyes of primary care physicians providing palliative and/or end-of-life care. Language and cultural discordance means that the physician and patient do not speak the same language or are not from the same cultural background. Qualitative data from primary care physicians (n = 12–24) providing language-discordant end-of-life care to Francophone and/or Allophone older adults across different care models and diverse geographies in Ontario will be collected through semi-structured interviews. Reflexive thematic analysis will be used to report themes within the data and consider the influence of the social locations of the researcher and research participants, geographic considerations impacting service provision, and barriers imposed by differing primary care funding structures on the provision of palliative and end-of-life care for linguistic and cultural minority groups in Ontario. Findings from this study will identify the interconnections among language and cultural discordance, care model, geographic region, and physician perceptions of their combined effects on access to, and quality of, palliative and end-of-life care. This evidence will be key to informing clinical practice guidelines and mobilizing change to improve primary care access and quality for adults at the end-of-life from linguistic and cultural minority populations across Ontario. Keywords: language discordance, qualitative research, reflexive thematic analysis, palliative care, primary care physicians, semi-structured interviews

Collective Identity Profiles: The Case of Francophones in Manitoba - Levesque, Annabel; Gueye, N’deye Rokhaya; Rivard, Étienne; de Moissac, Danielle; Archambault, Hélène (Minorités linguistiques et société / Linguistic Minorities and Society, 2023)
Abstract This quantitative study seeks to explore collective identity profiles that emerge among French-speaking adolescents and young adults in Manitoba. A total of 493 participants completed a questionnaire measuring their level of identification with Francophone and Anglophone identities, their perception of continuity with respect to the future of the French language and culture in Manitoba, and their mental wellbeing. The results of a cluster analysis revealed four collective identity profiles, namely Bilingual Optimist, Franco-Dominant Optimist, Indifferent Pessimist, and Anglo-Dominant Pessimist. Participants who belonged to each of these profiles differed in terms of their age, their mother tongue, the type of school they attended, and their gender. Moreover, collective identity profiles were linked to participants’ mental wellbeing, with those in the Bilingual Optimist profile and those in the Franco-Dominant Optimist profile demonstrating a significantly higher level of mental wellbeing compared to the other two profiles. Keywords: collective identity profiles, mental wellbeing, Francophone minorities, adolescence, young adulthood Résumé Cette étude quantitative visait à explorer les profils identitaires collectifs qui émergent naturellement chez les adolescents et les jeunes adultes francophones du Manitoba. Un total de 493 participants ont rempli un questionnaire mesurant leur niveau d'identification aux identités francophone et Anglophone, leur perception de continuité quant à l'avenir de la langue et de la culture françaises au Manitoba, et leur bien-être mental. Les résultats d'une analyse de classification ont révélé quatre profils identitaires collectifs émergeant, soit Bilingue optimiste, Franco-dominant optimiste, Indifférent pessimiste et Anglo-dominant pessimiste. Les participants appartenant à chacun de ces profils se distinguent par leur âge, leur langue maternelle, le type d'école qu'ils fréquentent et leur genre. De plus, les profils identitaires collectifs étaient liés au bien-être mental des participants, avec ceux du profil Bilingue optimiste et ceux du profil Franco-dominant optimiste ayant un niveau de bien-être mental significativement plus élevé par rapport aux deux autres profils. Mots-clés : profils identitaires collectifs, bien-être mental, minorités francophones, adolescents et jeunes adultes

L’expérience d’un échec à l’examen professionnel infirmier NCLEX-RN des diplômées d’un programme ontarien francophone de Baccalauréat en sciences infirmières - McGee, Shannon; Larocque, Sylvie; Pilon, Roger (Diversity of Research in Health Journal / Revue de la diversité de la recherche en santé, 2023)
Résumé En 2015, l’examen canadien d’admission à la profession infirmière a changé de format et est devenu similaire à celui des États-Unis. Les premiers résultats canadiens à l’examen d’admission NCLEX-RN ont démontré de nombreux échecs, qui touchaient davantage les francophones. Le but de la recherche était de décrire l’expérience de cet échec par des diplômées d’un baccalauréat ontarien en sciences infirmières francophone. Un devis qualitatif de type phénoménologique a été retenu comportant des entrevues individuelles semi-dirigées. La méthode d’analyse de Giorgi a été effectuée. Les résultats ont démontré que les participantes francophones ont vécu des difficultés supplémentaires peu importe la langue choisie qui, entre autres, a résulté à un ou plusieurs échecs de cet examen. L’impact d’un échec est dévastateur pour ces candidates et a des répercussions négatives sur les programmes de sciences infirmières francophones ainsi que sur l’accès au service de santé en français. Mots-clés :NCLEX-RN, examen d’autorisation, sciences infirmières, francophone, échec. Abstract In 2015, the Canadian nursing licensing exam changed its format and became similar to that of the United States. Initial results for the Canadian NCLEX-RN licensing exam demonstrated numerous failures, with Francophones failing at a greater rate. The aim of this study was to describe the experience of the NCLEX-RN exam failure by French-speaking Bachelor of Science Nursinggraduates of an Ontario program. A qualitative phenomenological design was chosen, comprising semi-structured individual interviews. Analysis of all interviews was completed using the Giorgi method. Results demonstratedthat French-speaking participants experienced additional difficulties regardless ofif they wrote the exam in French or English and were also more likely to experience one or more failures of this exam. The impact of failure has been described as devastating by participants of the study. Furthermore, the failure rates have had negative repercussions on Francophone nursing programs and can negatively impact access to healthcare services in French. KeyWords: NCLEX-RN, Nursing, Francophone, Fail, Licensing exam

Living in a liminal space: Experiences of 2SLGBTQ + official language minority Canadians during the COVID-19 pandemic - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Hardy, Stephan; Avanthay-Strus, Jacqueline (Culture, Health & Sexuality, 2023)
The intersecting identities of those identifying with multiple minorities, such as 2SLGBTQ + and ethnolinguistic minorities, bring individuals to have unique experiences, especially concerning health and wellness. This topic is particularly poorly understood among French-speaking official language minority 2SLGBTQ + populations in Canada. Hence, this study was conducted to generate insights into their needs and experiences, through the lens of intersectionality. This quantitative community-based study, a first of its kind in Western Canada, describes the sociodemographic profile, experiences of discrimination and stigmatisation, and needs and challenges pertaining to mental health and social supports of this double minority group. Data were obtained by an online survey conducted in the Canadian province of Manitoba in June 2020. The participant sample was largely homogenous: most were under the age of 55 years, white, educated, and from urban areas. Many reported experiencing dual marginalisation, feeling unaccepted by both of their minority communities (Francophone and 2SLGBTQ+). A sense of isolation, as well as a lack of social connectedness and psychological support, were often reported. Social initiatives and mental health support within environments proactively affirming of the official language of the minority and inclusive of diverse 2SLGBTQ + identities are needed.

Well-being and language: language as a well-being objective in Wales - Prys, Cynog; Matthews, David (Current Issues in Language Planning, 2023)

Report on the 2020–2023 Café de Paris Manitoba Pilot Project - Roberge, Jérémie (Santé en français Manitoba, 2023)
Nombre de pages: 28

Educating future physicians for francophone official language minority communities in Canada: a case study - Schrewe, Brett; Yeuchyk, Tatiana; El Hafid, Melanie; Nyhof-Young, Joyce (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Résumé Contexte: Plus d’un million de Canadiens francophones vivent dans des communautés de langue officielle en situation minoritaire (CLOSM) hors Québec. L’accessibilité de soins linguistiquement appropriés aux CLOSM est limitée. Par conséquent, la qualité des services qui leur sont offerts en souffre.Le programme FrancoDoc a été créé en 2015 pour aider à combler cette lacune sur le plan de l’équité en matière de santé. Il vise à offrir aux étudiants en médecine francophones ou francophiles dont l’anglais est la principale langue d’enseignement les moyens d’améliorer leurs compétences en français médical. Cependant, on sait peu de choses sur les possibilités et les limites de cette initiative éducative. Méthodes: Notre étude qualitative instrumentale de cas unique a exploré les expériences des participants au programme FrancoDoc, tout en examinant les facteurs qui influencent la prestation de services de santé linguistiquement appropriés aux CLOSM. Nous avons mené des entrevues semi-structurées avec des étudiants en médecine de tout le Canada et nous en avons analysé le contenu thématiquement en utilisant une approche réflexive et inductive. Résultats: Quatre thèmes principaux ont été dégagés des 12entrevues réalisées: les facteurs facilitant l’apprentissage du français; les obstacles à l’apprentissage du français; les facteurs contextuels influençant la prestation de soins de santé linguistiquementappropriés; et les recommandations visant à améliorer l’enseignement en soins de santé de manière à préparer les apprenants à servir les CLOSM. Conclusions: Bien que très motivés par le programme FrancoDoc, les étudiants participants se heurtent à des obstacles comme les contraintes de temps, la programmation irrégulière des activités, le manque d’occasions d’apprentissage clinique régulier et la réticence des facultés de médecine. Or, pour remplir leurs obligations envers les CLOSM qu’elles servent, il est essentiel que les facultés de médecine reconnaissent la langue comme un déterminant social spécifique de la santé et qu’elles offrent un soutien solide aux initiatives comme le programme FrancoDoc. Abstract Background: Over one million Francophone Canadians live in official language minority communities (OLMC) outside of Québec. Availability and accessibility of linguistically appropriate care to these OLMCs is lacking, resulting in poorer quality of care. To help address this health equity gap, the FrancoDoc program was created in 2015 to identify Francophone/Francophile medical students enrolled at medical faculties that use English as their primary language of instruction and equip them with skills to increase their medical French abilities. Little is known, however, about the affordances and limitations of this educational endeavour. Methods: Our qualitative instrumental single case study explored participants’ experiences with FrancoDoc, while also examining factors shaping the delivery of linguistically appropriate healthcare services to OLMCs. We conducted semi-structured interviews with medical students from across Canada and thematically analyzed these using a reflexive, inductive approach. Results: Four main themes were derived from 12 interviews: factors facilitating French language learning; barriers to French language learning; contextual factors shaping linguistically appropriate healthcare provision; and recommendations to improve healthcare education to better prepare learners to provide care to OLMCs. Conclusions: Medical student participants are highly motivated to engage in educational activities linked to FrancoDoc. Their efforts are nonetheless frequently impeded by barriers such as time constraints, irregular event programming, lack of regular clinical learning opportunities, and lukewarm support from faculties of medicine. If medical faculties are to realize their obligations to the OLMCs that they serve, recognition of language as a specific social determinant of health and more robust institutional supports for initiatives like FrancoDoc are paramount.

The gendered migrant experience: a study of family language policy (FLP) amongst mothers and daughters in the Somali community, Bristol - Selleck, Charlotte (Current Issues in Language Planning, 2023)

Portrait statistique sociosanitaire de la population immigrante de l’Ouest et du Nord - Sociopol (Santé en français, 2023)
Le présent document pourra être utile aux parties prenantes de la santé des personnes immigrantes en contexte francophone minoritaire. Il vise à outiller ce public à mieux comprendre certaines dimensions du profil sociodémographique et sociosanitaire des personnes immigrantes en contexte francophone minoritaire. Pour ce faire des statistiques sont présentées sous forme de tableau et de graphique, puis interprétées de manière sommaire. Les géographies retenues sont les provinces de l’Ouest et les territoires : Manitoba, Saskatchewan, Alberta, Colombie-Britannique, Yukon, Territoires-du-Nord-Ouest, Nunavut. La principale variable linguistique utilisée est la population ayant le français comme première langue officielle parlée (PLOP). La population immigrante récente réfère aux personnes qui ont obtenues leur résidence permanente entre 2016 et 2021.
Nombre de pages: 33

Francophone immigration to minority communities: Towards a bold, strong and coordinated approach - Standing Senate Committee on Official Languages (Sénat du Canada / Senate of Canada, 2023)
The demographic weight of the Canadian Francophonie is declining. The survival and vitality of francophone minority communities depends largely on immigration. In this report, the Standing Senate Committee on Official Languages provides an overview of the situation and stakeholders’ concerns regarding francophone immigration to minority communities, which has been the focus of several federal commitments in recent years. The Senate Committee also makes 12 recommendations based on briefs and witness testimony received from more than 50 stakeholders from a variety of backgrounds. Although the report does not focus specifically on the health sector, several of the points raised in the report concern the necessity of paying particular attention to the needs for French-speaking workers in the education, early childhood and health sectors.
Number of pages: 80

Recruiting service providers with French proficiency: Tips and strategies - The Knowledge Institute on Child and Youth Mental Health and Addictions (2023)
This report is designed as a resource to support the "Kids Come First Health Team" in developing a strategy for recruiting, retaining and training human resources in Ontario’s Champlain health region. The report has been prepared by the Knowledge Institute on Child and Youth Mental Health and Addictions (the Knowledge Institute). The Knowledge Institute builds connections, shares knowledge and draws on expertise to enhance the skills of direct service providers and agencies across Ontario in order to strengthen Ontario’s mental health programs and services for all children, young people, families and caregivers. We wanted to discover what organizations are doing — particularly organizations in the health sector — to recruit service providers with French proficiency. We also wanted to learn about evidence-based practices for recruitment from the literature. The strategies and guiding principles provided in this resource were derived from an environmental scan that included a rapid, nonsystematic literature review. As well, we consulted with key stakeholders and leaders in the field who have direct experience with recruiting service providers with French proficiency.
Number of pages: 22

Évaluation de la fidélité interjuges d’une grille d’observation des comportements d’offre active de services en français dans le cadre d’activités d’apprentissage par simulation - Vincent, Coralie; Bodnaruc, Alexandra Maria; Savard, Jacinthe; Kengneson, Cris-Carelle; Benoît, Josée; Giroux, Isabelle (Minorités linguistiques et société / Linguistic Minorities and Society, 2023)
Résumé Dans les régions canadiennes où les communautés francophones vivent en situation minoritaire, l’offre active (OA) de services en français consiste à proposer des services en français de façon proactive et dès le premier contact. Dans le contexte des services sociaux et de santé, l’OA contribue à la qualité, à la sécurité et à l’équité des soins destinés à ces communautés. La Grille d’observation des indicateurs de compétence en OA a été créée pour évaluer cette compétence chez les futurs professionnels dans un contexte d’apprentissage par simulation. Le présent projet de recherche visait à poursuivre l’évaluation métrologique de la grille en mesurant sa fidélité interjuges grâce au coefficient de corrélation intraclasse (CCI). Les résultats ont démontré un niveau de fidélité globale élevé (CCI = 0,87), ce qui permet d’encourager l’utilisation de la grille dans les milieux d’apprentissage. Des recherches supplémentaires permettront d’évaluer la fidélité de la grille dans divers contextes et d’assurer l’amélioration continue de la formation des futurs professionnels sur l’OA. Mots-clés : outils d’évaluation, offre active de services en français, formation des professionnels de la santé, apprentissage par simulation, fidélité interjuges Abstract In Canadian Francophone minority communities, the active offer (AO) of French language services involves proactively offering services in French from the first point of contact. In the context of health and social services, the AO contributes to the quality, safety and equity of care within these communities. The AO Competency Indicator Observation Grid was created to assess AO competency among future professionals in a simulated learning environment. The purpose of this research project was to continue the metrological evaluation of the grid by measuring its inter-rater reliability using the intraclass correlation coefficient (ICC). The results demonstrated a high level of global reliability (ICC = 0.87), thus supporting the use of the grid in learning environments. Further research will evaluate the reliability of the grid in a variety of settings and ensure continued improvement in the training of future professionals on the AO. Keywords: assessment tools, active offer of French language services, health professional education, simulated learning, inter-rater reliability

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.